Evaluation of the Climate Village Program to Improve Environmental Health - Ismike Suci; Nurhasan Syah; Indang Dewata; Iswandi Iswandi (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Climate change has a wide impact on the lives of people who are vulnerable to multidimensional disasters. Government efforts in tackling the impacts of climate change through the climate village program as implemented in Korong Pasa Surau Nagari Guguak, Padang Pariaman Regency. The study intends to measure the degree of success achieved in implementing community-based solutions for adaptation and mitigation in response to the challenges posed by climate change. The current investigation is a qualitative descriptive study conducted between March and April 2023.The participants for this study were recruited using a random chance sampling technique to verify that the selected individuals could adequately represent their respective groups. A cohort of five individuals was engaged as informants. The study's findings suggest evaluating the implementation of the climatic village program (Proklim) in Nagari Guguk Korong Pasa Surau. The assessment was carried out by considering the several elements of the climate village program activities, which encompassed adaptation activities aimed at addressing climate change (74.33%), climate change mitigation actions (17.33%), and an evaluation of the institution's sustainability and support (14.50%). The circumstance above demonstrates that the proklim in Nagari Guguak Korong Pasa Surau falls inside the moderately effective classification. In the future, to increase the success and sustainability of Proklim in the area, multisector support is needed so that Proklim can make its people able to adapt and mitigate climate change and create good environmental health